Political Fund ballot - CWU poster, 1995 (London, 1995)
1995 1980-95 "Political Fund ballot - CWU poster, 1995" [BW0179], 1995, Trades Union Congress The Trade Union Act 1984 required trade unions to ballot their members every ten years for approval to continue to operate their respective political funds. The Communications Workers Union produced this poster as part of its 1995 ballot campaign.